A head‐to‐head comparison of ixekizumab vs. guselkumab in patients with moderate‐to‐severe plaque psoriasis: 24‐week efficacy and safety results from a randomized, double‐blinded trial*. (1st June 2021) - Blauvelt, A.; Leonardi, C.; Elewski, B.; Crowley, J.J.; Guenther, L.C.; Gooderham, M.; Langley, R.G.; Vender, R.; Pinter, A.; Griffiths, C.E.M.; Tada, Y.; Elmaraghy, H.; et al.
Summary: Background: Significantly more patients with moderate‐to‐severe plaque psoriasis treated with the interleukin (IL)‐17A inhibitor ixekizumab vs. the IL‐23p19 inhibitor guselkumab in the IXORA‐R head‐to‐head trial achieved 100% improvement in Psoriasis Area and Severity Index (PASI 100) at week 12. Objectives: To compare skin and nail clearance and patient‐reported outcomes for ixekizumab vs. guselkumab, up to week 24. Methods: IXORA‐R enrolled adults with moderate‐to‐severe plaque psoriasis, defined as static Physician's Global Assessment ≥ 3, PASI ≥ 12 and involved body surface area ≥ 10%. Statistical comparisons were performed using the Cochran–Mantel–Haenszel test stratified by pooled site. Time‐to‐first‐event comparisons were performed using Kaplan–Meier analysis, and P ‐values were generated using adjusted log‐rank tests stratified by treatment group. Cumulative days at clinical and patient‐reported responses were compared by ancova . The trial was registered with ClinicalTrials.gov (NCT03573323). Results: Of the 1027 patients randomly assigned, 90% completed the trial (465 of 520 ixekizumab and 459 of 507 guselkumab). As early as week 2 and through week 16, more patients on ixekizumab achieved PASI 100 ( P < 0·01). At week 24, ixekizumab was noninferior to guselkumab (50% vs. 52%, difference −2·3%), with no statistically significant difference in PASI 100 ( P = 0·41). More patients receiving ixekizumab showed completely clear nails at week 24 (52% vs. 31%, P = 0·007). The median time to first PASI 50/75/90 and PASI 100 were 2 and 7·5 weeks shorter, respectively, for patients on ixekizumab vs. guselkumab ( P < 0·001). Patients on ixekizumab also had a greater cumulative benefit, with more days at PASI 90 and 100, with Dermatology Life Quality Index of 0 or 1, and itch free ( P < 0·05). The frequency of serious adverse events was 3% for each group, with no new safety signals. Conclusions: Ixekizumab was noninferior to guselkumab in complete skin clearance and superior in clearing nails at week 24. Ixekizumab cleared skin more rapidly in patients with moderate‐to‐severe plaque psoriasis, with a greater cumulative benefit, than guselkumab. Overall, the safety findings were consistent with the known safety profile for ixekizumab. Abstract: What is already known about this topic? Patients with plaque psoriasis desire both high levels of clearance and rapid onset of treatment effects. Ixekizumab is a high‐affinity monoclonal antibody that selectively targets interleukin (IL)‐17A. In the 12‐week report of the IXORA‐R study, ixekizumab demonstrated significantly higher efficacy at early timepoints than the IL‐23p19 inhibitor guselkumab, with more patients achieving 100% improvement in Psoriasis Area and Severity Index (PASI 100) and improved quality of life as early as week 4. What does this study add? Patients on ixekizumab vs. guselkumab achieved similar levels of skin clearance and superior efficacy in the resolution of nail psoriasis at week 24. Patients on ixekizumab vs. guselkumab had a greater cumulative benefit, with more days at PASI 90 and 100, more days when psoriasis did not impact their quality of life, and more itch‐free days. The safety profiles of both drugs were consistent with those in previous studies. Linked Comment: Puig. Br J Dermatol 2021; 184 :992–993 .